Kepemimpinan Virtual sebagai Alternatif Mempertahankan Budaya Mutu Pondok Pesantren pada Masa Normalitas Baru Pandemi Covid-19 - Agustian Ramadana Putera (Universitas Negeri Jakarta, 2022)
This research is a qualitative study that aims to analyze the application of virtual leadership to boarding schools in Indonesia in an effort to maintain a quality culture in the new normality of the Covid-19 pandemic. This study is a literature study that analyzes sources from previous studies on virtual leadership and its relationship to the Covid-19 pandemic. The method of data collection is done in several stages, namely sorting, organizing, and editing. After the data in the form of the documents in question collected then done data analysis by providing interpretation. The results of this study is divided into several section that include: 1) effective leadership in the period and post-Covid-19 pandemic, 2) kyai and its potential to lead a virtual environment, 3) the state and quality of boarding schools after the Covid-19 pandemic.